The Modern Battlefront of Natural History and the Emergence of Animal Heroes - Genosko, Gary (UnderCurrents: Journal of Critical Environmental Studies, 1991)
The popular nature writer and conservationist Ernest Harold Baynes (1868-1925) was instrumental in bringing the issue of the place of animals in war to the attention of nature historians in the United States. In Animal Heroes of the Great War,1 Baynes presented a general overview of the use of animals in the Allied war effort of World War I, describing the service of horses, camels, mules, donkeys, oxen, dogs and pigeons. As a representative of Harper's magazine, he travelled through England, France, Belgium, Italy, Egypt and Palestine from the winter of 1919 to the summer of 1920, collecting material for Animal Heroes and "Our Animal Allies in the World War," which appeared in Harper's in 1921.2